Answer:
[tex]x - 4y = - 6 \: ......(1) \\ \\ 2x + 3y = 10 \: .......(2)[/tex]
from equation (1)
[tex]x - 4y = - 6 \\ \\ 4y = x + 6 \\ \\ y = \frac{x + 6}{4} [/tex]
Substitute " y " in equation (2)
[tex]2x + 3y = 10 \\ \\ 2x + 3( \frac{x + 6}{4} ) = 10 \\ \\ 2x +( \frac{3x + 18}{4} ) = 10 \\ \\ \\ \frac{8x + 3x + 18}{4} = 10 \\ \\ \\ 8x + 3x + 18 = 10 \times 4 \\ \\ 11x + 18 = 40 \\ \\ 11x = 40 - 18 \\ 11x = 22 \\ \\ x = \frac{22}{11} \\ \\ x = 2[/tex]
[tex]y = \frac{x + 6}{4} \\ \\ y = \frac{2 + 6}{4} \\ \\ y = \frac{8}{4} \\ \\ y = 2[/tex]